2012
DOI: 10.1095/biolreprod.111.097030
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane Ameliorates Doxorubicin-Induced Injury in Mouse Ovarian Cells1

Abstract: Doxorubicin (DXR) is a frontline chemotherapy agent implicated in unintended ovarian failure in female cancer survivors. The fertility preservation techniques currently available for cancer patients are often time and cost prohibitive and do not necessarily preserve endocrine function. There are no drug-based ovary protection therapies clinically available. This study provides the first investigation using dexrazoxane (Dexra) to limit DXR insult in ovarian tissue. In KK-15 granulosa cells, a 3-h DXR treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 56 publications
1
48
0
1
Order By: Relevance
“…The 20 mg/kg Dexra dose represents a 1:1 Dexra/DXR mg ratio, providing a significant dose reduction from that used in cardioprotection to limit potential side effects of Dexra. The chosen Dexra dose was based on our previous in vitro study demonstrating a 2 μM Dexra dose, 100-folds lower than that used in in vitro cardiac protection studies, preserved granulosa cell viability against DXR [ 23 ]. Animals were euthanized with CO 2 followed by cervical dislocation and ovaries removed surgically 0, 2, 4, 10, 12 or 24 h after the second injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 20 mg/kg Dexra dose represents a 1:1 Dexra/DXR mg ratio, providing a significant dose reduction from that used in cardioprotection to limit potential side effects of Dexra. The chosen Dexra dose was based on our previous in vitro study demonstrating a 2 μM Dexra dose, 100-folds lower than that used in in vitro cardiac protection studies, preserved granulosa cell viability against DXR [ 23 ]. Animals were euthanized with CO 2 followed by cervical dislocation and ovaries removed surgically 0, 2, 4, 10, 12 or 24 h after the second injection.…”
Section: Methodsmentioning
confidence: 99%
“…In a proof-of-concept study using immortalized KK-15 mouse granulosa cells, we demonstrated that Dexra protects granulosa cells from DXR-induced DNA damage and cytotoxicity in vitro in a manner consistent with inhibiting TOPII DNA cleavage, rather than oxidative stress [ 23 ]. Furthermore, Dexra treatment of in vitro- cultured mouse and marmoset ovaries prior to DXR administration reduced the number of dsDNA breaks, and rescued primary granulosa cell viability [ 23 , 24 ]. The data demonstrated the potential for Dexra to be an effective ovoprotective agent against DXR toxicity by blocking the initial insult as well as subsequent cellular demise.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-genotoxic effects of dexrazoxane against doxorubicin in mouse ovarian cells were also reported (40). Their results revealed the ability of dexrazoxane to inhibit the topoisomerase II catalytic activity, to reduce double-strand DNA breaks and, thus, to prevent genotoxicity.…”
Section: Discussionmentioning
confidence: 91%
“…The largest follicles were punctured to obtain oocytes and granulosa cells (Cheng et al, ). Theca cells cells were isolated by 30‐min treatment with 0.25% collagenase at 37°C followed by cell dispersion using a 23‐Gauge needle (Roti Roti & Salih, ). Bone marrow mesenchymal cells were flushed out from the tibial and femoral bones of donor adult female rats using a syringe and 20‐Gauge needle (Wei, Fraser, Lu, Hu, & Yu, ).…”
Section: Methodsmentioning
confidence: 99%